Arthritic Microenvironment Actuated Nanomotors for Active Rheumatoid Arthritis Therapy. Issue 4 (14th November 2022) - Xu, Cong; Jiang, Yuejun; Wang, Hong; Zhang, Yuxin; Ye, Yicheng; Qin, Hanfeng; Gao, Junbin; Dan, Qing; Du, Lingli; Liu, Lu; Peng, Fei; Li, Yingjia; et al.
Abstract: Increasing O2 demand and excessive ROS production are the main features of arthritic microenvironment in rheumatoid arthritis (RA) joints and further play pivotal roles in inflammation exacerbation. In this work, a system of in situ regulation of arthritic microenvironment based on nanomotor strategy is proposed for active RA therapy. The synthesized MnO2 ‐motors enable catalytic regulation of RA microenvironment by consuming the overproduced H2 O2 and generating O2 synergistically. The generated O2 under H2 O2 ‐rich conditions functions as inflammation detector, propellant for enhanced diffusion, as well as ameliorator for the hypoxic synovial microenvironment. Owing to O2 generation and inflammation scavenging, the MnO2 ‐motors block the re‐polarization of pro‐inflammatory macrophages, which results in significantly decreased secretion of multiple pro‐inflammatory cytokines both in vitro and in vivo. In addition, intra‐articular administration of MnO2 ‐motors to collagen‐induced arthritis rats (CIA rats) effectively alleviates hypoxia, synovial inflammation, bone erosion, and cartilage degradation in joints. Therefore, the proposed arthritic regulation strategy shows great potential to seamlessly integrate basic research of RA with clinical translation. Abstract : In this work, a system of in situ regulation of arthritic microenvironment based on nanomotor strategy is proposed for active RA therapy. The synthesized MnO2 ‐motors enable catalytic regulation of RA microenvironment by consuming the overproduced H2 O2 and generating O2 synergistically. This arthritic microenvironment powered nanomotor system simultaneously integrates hypoxia relief and ROS scavenging for macrophages phenotypic regulation.